Environmental Accounting: A Scientometric using Biblioshiny - Taqi, Muhamad; Rusydiana, Aam Slamet; Kustiningsih, Nanik; Firmansyah, Irman (International Journal of Energy Economics and Policy, 2021)
This study aims to determine the development of research trends on environmental accounting published by national and international journals. The data analyzed consists of 500 indexed research publications during the period 1981 to 2020. The data is then processed and analyzed using the R Bibliometric application to determine the bibliometric map of environmental accounting developments. The results showed that the number of publications on the development of the role of research related to environmental accounting has increased significantly. Then, the most common type of document that analyzes environmental accounting is journal articles. The most popular writer was Wood R, who during the research period he consistently conducted research on this theme, and the most popular keywords were energy, environmental and assessment. Keywords: Environmental Accounting, Energy, Bibliometrics R JEL Classifications: Q56, Q50, M41 DOI: https://doi.org/10.32479/ijeep.10986